2023
DOI: 10.1021/acsestwater.2c00404
|View full text |Cite
|
Sign up to set email alerts
|

Unique Geochemistry of Arsenic-Contaminated Groundwater and Corresponding Mitigation Efforts in Southern Nepal

Abstract: In the lowlands of Nepal, as well as in several other South Asian countries, the level of arsenic in groundwater extracted from Quaternary alluvial sediments frequently exceeds the World Health Organization (WHO) drinking water guideline of 10 μg/L. The widely accepted explanation refers to the reductive dissolution of Fe-bearing minerals releasing As-oxyanions from the soil minerals. However, this hypothesis is only to some extent applicable. Given that arsenic and iron in the groundwater are weakly correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
(180 reference statements)
0
2
0
Order By: Relevance
“…The finding of the study confirmed the negligible impact of Cl − , SO 4 2− , and NO 3 − on the arsenic adsorption process at both low and high concentrations. The presence of HCO 3 − and PO 4 3− has negligible interference when present at low concentration (<1 mg L −1 ); however, it affects the removal efficiency at high concentrations (at 10 mg L −1 of phosphate and 500 mg L −1 of bicarbonate).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of the study confirmed the negligible impact of Cl − , SO 4 2− , and NO 3 − on the arsenic adsorption process at both low and high concentrations. The presence of HCO 3 − and PO 4 3− has negligible interference when present at low concentration (<1 mg L −1 ); however, it affects the removal efficiency at high concentrations (at 10 mg L −1 of phosphate and 500 mg L −1 of bicarbonate).…”
Section: Resultsmentioning
confidence: 99%
“…Arsenic contamination of groundwater is undoubtedly one of the detrimental global issues that mankind is suffering from. Since its first report in the early 1980s, more than 150 million people worldwide have been reported to be exposed, and the spread of arsenic contamination in groundwater has continued to grow with every new survey. , Considering the serious health risks associated with chronic consumption of arsenic-contaminated water, such as hypertension, keratosis, and skin and bladder cancer, the development of a robust arsenic removal technology is of a pressing need.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a growing interest in the applications of Fe 0 for environmental remediation [14,22,23] and safe drinking water supply [87][88][89][90], little progress has been made in characterizing the variability in reactivity among Fe 0 samples from different sources [19,34,86,91,92]. The most important lesson from Figure 5 is that the extent to which saltwater affects the performance of a Fe 0 /H 2 O system depends on the used Fe 0 source used (Fe 0 quality).…”
Section: Influence Of Fe 0 Dosage On Dye Discoloration In Fe 0 /H 2 O...mentioning
confidence: 99%
“…While this difference is difficult to justify, the overall results reaffirm the importance of characterizing the diversity among the Fe 0 materials of environmental interest (Miehr et al 2004. Despite a growing interest in the applications of Fe 0 for environmental remediation (Guan et al 2015, Plessl et al 2022, Singh et al 2023) and safe drinking water supply (Tepong-Tsindé et al 2019, Tepong-Tsindé 2021, Mueller et al 2023, little progress has been made in characterizing the variability in reactivity among Fe 0 samples from different sources , Ranjan et al 2006, Naseri et al 2017. The most important lesson from Figure 5.5 is that the extent to which saltwater affects the performance of a Fe 0 /H2O system depends on the used Fe 0 source used (Fe 0 quality).…”
Section: Influence Ofmentioning
confidence: 84%
“…Currently, Fe 0 -based filtration is also considered to be one of the most affordable and applicable technologies for decentralized safe drinking water supply (Naseri et al 2017, Noubactep 2018a, Mueller et al 2023, Bandyopadhyay 2024. In other words, the Fe 0 technology can significantly contribute to achieving the two United Nations (UN) Sustainable Development Goals (SDGs) focusing explicitly on freshwater: (i) Goal 6 "Ensure availability and sustainable management of water and sanitation for all", and (ii) Goal 14 "Conserve and sustainably use the oceans, seas and marine resources for sustainable development" (Hering et al 2016).…”
Section: Introductionmentioning
confidence: 99%